La primatologie comme vecteur d’éducation à la citoyenneté - Patrick Renault; Valérie Ribaute-Maunier (Revue de Primatologie)
Centered around a scientific workshop in High School, pupils are encouraged to have a deeper look at the apes and the reason why they are threatened with extinction. From this new-found knowledge a civic awareness is born in the minds of the pupils and this leads them to share their findings and obtain improvements from decision makers and consumers alike.